In Vivo Near-Infrared Fluorescence Imaging of Aqueous Humor Outflow Structures. (24th May 2016) - Zeppa, L.; Ambrosone, L.; Guerra, G.; Fortunato, M.; Costagliola, C.
Abstract : The aim of this study has been to visualize the aqueous outflow system in patients affected by primary open angle glaucoma. A solution of indocyanine green (ICG) plus high viscosity viscoelastic solution was injected into the Schlemm canal during surgery in 10 glaucomatous patients undergoing canaloplasty. Soon after injection of the dye the borders of the scleral flap were completely stained due to partial reflux caused by the intrachannel resistance; progression of the dye along the Schlemm canal starting from the site of injection was then visualized. The filling of the collector channels was observed only in the patent portions of the Schlemm canal. The only noticeable aqueous veins were located in correspondence of the quadrant in which both the Schlemm canal and the collectors were patent. Lastly, a retrograde filling, of glomerular-shaped structures, deepest to the Schlemm canal was observed in the quadrants where the pathway was functioning. Our findings show that injection of a mixture composed of ICG and viscoelastic solution into the Schlemm canal allows a clear visualization of the functioning portions of the conventional outflow pathway. In addition, a retrograde filling of structures presumably located into the iris was also recorded. Clinical Trial Registration . Our study is registered in ISRCTN registry, number54005880, DOI 10.1186/ISRCTN54005880.